The Design Specificity of the Ammunition Supply and Storage Mechanism in Naval Weapon System OSU-35 - Zbigniew WÓJCIK; Tadeusz ŚWIĘTEK; Marcin ŁABNO (Problemy Mechatroniki)
The article presents the design of the ammunition supply and storage mechanism developed for the 35 mm Naval Cannon, which is an integral part of the Naval Weapon System OSU-35. The system for supplying and storing ammunition for the 35 mm KDA automatic naval cannon, was developed and manufactured in Zakłady Mechaniczne (Mechanical Plant) ‘Tarnów’ S.A. in Tarnów (Poland), as part of the project ‘35 mm Automatic Naval Cannon KDA with a Fire Control System Installed on the Ship Using the Sea Version of the ZGS-158 Integrated Tracking Head with Fire Control System’. The manufactured ammunition supply and storage mechanism used in the 35 mm Naval Cannon has been tested in the factory, military training area and verified in real conditions during research conducted at sea. The sea tests of the Naval Weapon System, installed on board of Polish anti-submarine corvette ORP Kaszub, were carried out in real conditions and included tests of shooting at surface and air targets at various parameters and distances to the target. The results of the tests carried out showed that the adopted design solutions met the assumptions that had been set and defined for the development of the 35 mm Naval Cannon, which is an integral part of the Naval Weapon System.